2015
DOI: 10.1007/s00784-015-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

An oral health survey of vulnerable older people in Belgium

Abstract: In the long term, the most important future challenge of oral health care policies is to identify older adults before they begin to manifest such oral health deterioration. Regular dental visits should be strongly promoted by all (oral) health care workers during the lifespan of all persons including older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 28 publications
10
46
7
Order By: Relevance
“…The results suggest that oral status and (self‐reported) oral health point toward a positive impact of oral health on healthy aging as edentulous elderly when compared with elderly with remaining teeth reported more frailty, used more medicines, and had a lower QoL and worse ADL. These observations are comparable with those of Watanabe et al () who concluded that frail older individuals had significantly poorer oral function than prefrail and robust individuals and De Visschere et al () who stated that care dependency was influenced by oral health parameters. In line with this observation, elderly with implant‐supported overdentures performed better too.…”
Section: Discussionsupporting
confidence: 90%
“…The results suggest that oral status and (self‐reported) oral health point toward a positive impact of oral health on healthy aging as edentulous elderly when compared with elderly with remaining teeth reported more frailty, used more medicines, and had a lower QoL and worse ADL. These observations are comparable with those of Watanabe et al () who concluded that frail older individuals had significantly poorer oral function than prefrail and robust individuals and De Visschere et al () who stated that care dependency was influenced by oral health parameters. In line with this observation, elderly with implant‐supported overdentures performed better too.…”
Section: Discussionsupporting
confidence: 90%
“…Although the compromised oral health of the institutionalized seniors is addressed in cross‐sectional research, little information is available on the effect of intervention to improve oral health. The purpose of such intervention is, usually, education of nursing home staff in oral health and implementation of recall programmes for the residents .…”
Section: Introductionmentioning
confidence: 99%
“…4 There are, furthermore, correlations between reduced oral health and such general medical issues as arteriosclerosis, 5 infection-related disorders 6 and pneumonia. 7 Although the compromised oral health of the institutionalized seniors is addressed in cross-sectional research, 2,8,9 little information is available on the effect of intervention to improve oral health. The purpose of such intervention is, usually, education of nursing home staff in oral health and implementation of recall programmes for the residents.…”
Section: Introductionmentioning
confidence: 99%
“…Care‐dependent individuals often lack the cognitive and physical abilities to perform adequate oral hygiene and to access professional dental care . As a result, oral health of care‐dependent individuals is generally poor . Compromised oral health causes pain and discomfort, which in turn is related to low oral health‐related quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 As a result, oral health of care-dependent individuals is generally poor. 7,8 Compromised oral health causes pain and discomfort, which in turn is related to low oral health-related quality of life. 9,10 It is also associated with a number of systemic diseases, [11][12][13] deteriorated physical [14][15][16] and cognitive performance, [17][18][19] depression, 20 institutionalisation, 21 and even mortality 22,23 in frail individuals.…”
Section: Introductionmentioning
confidence: 99%